2019
DOI: 10.3892/or.2019.7305
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of sarcosine dehydrogenase (SARDH) loci as a prognosticator for renal cell carcinoma

Abstract: DNA methylation plays an important role in the genesis and progression of tumor diseases. To identify new DNA methylation markers possibly associated with the clinical characteristics of renal cell carcinoma (RCC), we investigated loci in the sarcosine dehydrogenase (SARDH) gene. SARDH is involved in the metabolism of the glycine-derivative sarcosine and is closely linked through a functional control loop. Statistical evaluation of methylation data and clinical characteristics of patients showed that kidney tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Based on these findings, it could be inferred that SARDH is an oncogenic factor in HCC. The low expression of SARDH suggested a worse prognosis in HCC, as well as in other cancers like prostate cancer, colorectal cancer and renal cell carcinoma [17][18][19]. The study also constructed a nomogram that demonstrated SARDH had some predictive power for survival at 1, 3, and 5 years.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Based on these findings, it could be inferred that SARDH is an oncogenic factor in HCC. The low expression of SARDH suggested a worse prognosis in HCC, as well as in other cancers like prostate cancer, colorectal cancer and renal cell carcinoma [17][18][19]. The study also constructed a nomogram that demonstrated SARDH had some predictive power for survival at 1, 3, and 5 years.…”
Section: Discussionmentioning
confidence: 93%
“…While SARDH methylation has not yet been explored in the context of in HCC, it has been studied in renal cell carcinoma. SARDH hypermethylation was obviously related with the clinical aggressive characteristics and has been recognized as an important factor affecting recurrence-free survival in renal cell carcinoma 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, promoter CpG methylation of γ-catenin is considered an independent predictor for survival and disease progression [ 84 ]. Other hypermethylated genes associated with worse RCC disease-specific survival are: GATA Binding Protein 5 ( GATA5 ), that codify for a DNA-binding transcription factor [ 85 , 86 ]; Gremlin 1 ( GREM1 ), related to cytokine activity and bone morphogenic protein [ 87 ]; HIC ZBTB Transcriptional Repressor 1 ( HIC1 ), related both to DNA-binding transcription factor activity and histone deacetylase binding [ 88 ]; Junction Plakoglobin ( JUP ), related to protein homodimerization activity and protein kinase binding [ 84 ]; neural EGFL like 1 ( NELL1 ), linked to calcium ion binding [ 76 ]; Protocadherin 8 ( PCDH8 ), also related to calcium ion binding [ 89 ]; Phosphatase and Tensin Homolog ( PTEN ), related to protein kinase binding [ 90 ]; Ras Association Domain Family Member 1 ( RASSF1A ) that encodes a protein similar to the RAS effector proteins [ 91 , 92 ]; sarcosine dehydrogenase ( SARDH ), associated to oxidoreductase activity [ 93 ]; and Secreted Frizzled Related Protein 1 ( SFRP1 ), related to G protein-coupled receptor activity [ 94 , 95 ]. Very recently some methylated genes with prognostic value in pRCC have also been described [ 96 ].…”
Section: Epigenetics Of Clear Cell Renal Cell Carcinomamentioning
confidence: 99%
“…20 Glycine is an essential metabolite for nucleic acid synthesis, and the methylation sarcosine dehydrogenase gene related to a prognostic factor for recurrence-free survival in RCC patients. 21…”
Section: Evaluation Of Five Metabolites Of the Predictive Model In Intracellular Metabolism Based On In Vitro Analysis Of Rcc Cell Linesmentioning
confidence: 99%